Supervision And Enforcement of Criminal Laws for Cartels in the Digital Era According to Law Number 5 of 1999 Concerning Prohibition of Monopolistic Practices And Unfair Business Competition - Wuntu, Happy Ferovina (International Journal of Education, Information Technology, and Others, 2024)
Supervision and law enforcement as well as proof of cartel crimes in digital transactions face a number of complex challenges. where there is limited knowledge and technical capabilities of law enforcement in understanding and handling technological aspects used in digital cartel practices including the use of online platforms, encrypted messages, and digital trace erasure techniques designed to deceive investigators. This research uses a type of qualitative research with a normative juridical approach with a comparative approach, a normative research basis with study and analysis of Law Number 5 of 1999. Proving cartels is hampered due to the existence of business competition authorities and experiencing difficulties in proving the existence of cartel acts, by finding evidence of the existence of an agreement where business actors mutually agree to carry out cartel actions. Of course, perpetrators often have unwritten cartel agreements so that there is no physical evidence or direct evidence regarding the cartel crimes that have occurred. The highly secretive nature of cartels makes cartel actions a crime in the field of business competition that is difficult to detect for proof in the world and in the digital era. It can be concluded that the obstacle and cause of the ineffectiveness of monitoring and enforcing cartels in Indonesia in this digital era is that in Law no. 5 of 1999 does not recognize indirect evidence, so that evidence in judicial practice has different views regarding its position in the procedural law system that exists and applies in Indonesia. UU no. 5 of 1999 does not provide the KPPU with the authority to search and confiscate to obtain the necessary documents, both for business actors suspected of violating it and also for other related parties.